Corporate Social Responsibility of Chinese Manufacturing Companies’ effect on Green Business Strategy, Innovation and Performance - lI, Yan (Technium Social Sciences Journal, 2022)
The purpose of this paper is to study the influence of Chinese manufacturing companies in implementing corporate social responsibility, to verify how it affects environmental and export performance, and to explore the mediating effect of green business strategy and innovation. To this end, this paper uses structural equation modeling on a data set of 226 Chinese manufacturing companies to test the study hypotheses. The results show that CSR positively affects green business strategy, innovation, export and environmental performance. The results also support the partial mediation effect of green business strategy and innovation on the relationship between CSR, export and environmental performance. The findings may better help manufacturing enterprises understand how CSR, green business strategy, innovation are important forces for manufacturing companies to achieve outstanding business activities and contribute to social development.